Association Between Smoking and Oral Lichen Planus in Males - A Retrospective study - V, PADMAHARISH; RAMAMURTHY, JAIGANESH; GURUNATHAN, DEEPA (The journal of contemporary issues in business and government, 2021)
Oral lichen planus affects one to two percent of the general adult population and is the most common non‐infectious oral mucosal disease. Tobacco smoking increases the risk of OLP malignant transformation as cigarette smoke contains substances that induce chronic inflammation at mucosal surfaces. The aim of this study was to assess the association between smoking and oral lichen planus in males. A retrospective study was conducted using the case records of patients visiting a private dental college in Chennai from June 2019 - March 2020. The study population included case records of male patients with oral lichen planus, selected by non-probability purposive sampling. Data regarding their smoking habit were collected. Descriptive and inferential statistics were done using SPSS software. Among the study population, 43.59% of patients were below 40 years and 56.41% were above 40 years of age. About 53.8% of male patients with oral lichen planus had a smoking habit. Erosive lichen planus was the most common variant followed by the reticular type.Within the limits of the study, there was a significant association between smoking and oral lichen planus in males, with an increased incidence of erosive lichen planus among smokers.